Factors affecting the self-rated health of elderly individuals living alone: a cross-sectional study - Yoshimitsu, Koji (BMC Res Notes, 2017)
OBJECTIVE: In Japan, the number of elderly individuals living alone is continuing to increase as society ages. Although studies have considered quality of life, life expectancy, and gender differences in elderly individuals living alone, only a few have considered the health and lifestyle of these individuals. Therefore, we aimed to investigate the factors that affect the self-rated health of elderly individuals living alone to understand this group and how best to offer them support. RESULTS: We include 113 individuals. There was a significant difference (P < 0.05) in some characteristics (e.g., age, chronic illness, frequency of hospital visits in 1 month, and caregivers), activities of daily living (e.g., motor tasks), and instrumental activities of daily living (e.g., household affairs, heavy housework, outdoor household, and outdoor activities).